(untitled) (Bangladesh Journal of Agriculture, 2022)
The pandemic COVID-19 has adverse impacts in almost every sector, including agriculture and education. As an agricultural country, Bangladesh Govt. have prioritized the livelihood, socio-economic condition, especially the education programs in the haor areas. This study aimed to assess the impact of COVID-19 on academic performances of primary to higher secondary students in the haor areas of Netrokona and Sunamganj districts. A total of 620 individuals took part in this study. All the participants thought their academic performance were affected by the COVID-19 pandemic in varying degrees. Half of the respondents had no opportunity to join online learning during school closures due to COVID-19 lockdown. The majority of online learners (61.54%) used software-based online classes, while a significant amount of students (39.74%) watched only government-provided Bangladesh Television (BTV) classes during the lockdown. Numerous problems regarding online learning, like financial crisis, lack of smart gadgets, expensive and slow internet, lack of training etc., were predominantly identified in haor areas. It is recommended that concerned authorities should take initiative to provide study loans, free or cheaper data packages, training to teachers and motivation to students and guardians to overcome the temporary loss of education in haor areas of Bangladesh. The findings of this study might help the educationists and policymakers to implement pandemic recovery programs for rural development in the agricultural region of the country. Bangladesh J. Agri. 2019-2021, 44-46: 115-125